Bibliometric Analysis of Sukuk Literatures - Rezkyarta, Alif; Irfany, Mohammad Iqbal (Journal of Islamic Economics Literatures, 2023)
This study aims to see the development of research "Sukuk” around the world and research plans that can be carried out based on journals published on that theme. This study used a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Sukuk” which comes from the Scopus database with a total of 603 journal articles. The results of the study found that in the author mapping bibliometrics the author published the most research with the theme "Sukuk”Siswantoro. D. Furthermore, based on the bibliometric keyword mapping, there are 5 clusters that can become research lines with topics related to Sukuk, Development and Challenges of Sukuk, Bonds vs. Sukuk, Determinants of Sukuk, Sukuk as a Financial Instrument, Risks of Sukuk, the most used words are Sukuk, Development, and Bond